Managing Time In Education Organization: Policy Implications for Educational Managers in Rivers State, Nigeria - Elizabeth, Olawolu Oladunni; Nonye, Ahaiwe Christiana (Mediterranean Journal of Social Sciences, 2011)
The efficient use of time is an important variable in helping students achieve learning goals and making the classrooma pleasant place for teachers and students. Two research questions were used for the study. Population for the study was onehundred and twenty while the sample was sixty students and teachers through the use of simple sampling techniques to enableeach member of the population have equal opportunity of been selected. A time management questionnaire was used for thestudy. Two research questions were used and the researcher gave seven recommendation which will help the educationalmanager to manage their time well to enable them achieve their goals.